LIFESTYLE EDUCATION TO PREVENT CHRONIC DISEASES AMONG INDONESIAN MIGRANT WORKERS IN MALAYSIA: A COMMUNITY EMPOWERMENT - Tri Pudy Asmarawati; Lyndia Effendy; Jonny; Hartin Suidah; Husin Thamrin; Kusuma Scorpia Lestari; Baterun Kunsah; Dicky Faizal Irnandi; Heru Fajar Trianto (Journal of Public Health Research and Community Health Development, 2026)
Malaysia is a prominent destination for Indonesian migrant workers in Southeast Asia. Despite their economic importance, migrant workers are susceptible to chronic diseases, particularly hypertension and diabetes, due to constrained access to healthcare, unhealthy behaviors, and demanding working environments. The objective of this community service initiative included the assessment of the health status of Indonesian migrant workers and the promotion of awareness through screening and educational activities. This community service program was conducted in May 2024 at Sekolah Indonesia Kuala Lumpur, in collaboration with the NGO Sharing Organization and the Indonesian Embassy. A total of 113 migrant workers participated in the event. Screening included blood pressure measurement, random blood sugar testing, eye, and reproductive health examinations. Doctoral medical students delivered a mini seminar on chronic disease prevention and management. The majority of participants were women (57%) and within the productive age group (25-55 years). Hypertension was highly prevalent (54%). The mean random blood sugar was 138 ±62.5 mg/dL). Domestic work was the most common occupation. The participants demonstrated a strong interest in health education, and feedback indicated that regular health programs would be welcomed. Indonesian migrant workers in Malaysia show a high burden of hypertension and diabetes but limited disease awareness. Routine health screening, culturally appropriate education, and stronger collaboration between employers, health providers, and the Indonesian Embassy are essential to improve chronic disease prevention and sustain worker productivity.